La formation réciproque sur les questions de justice énergétique dans l’espace politique local: enjeux et possibilités - Laurence Brière; Maude Prud’homme; Guillaume Moreau; Isabel Orellana; Marie-Ève Marleau; Martine Chatelain (VertigO)
Municipal governments could play a leading role in the energy and ecological transition. In Quebec, the responsibilities devolved to the municipalities are indeed directly concerned with the “transition”. In addition, residents possess valuable knowledge about their local environment and its social network. In recent years, we observed a new enthusiasm for political engagement at the local level. That said, it appears that citizens and local elected officials know generally too little about the political, legal, and regulatory levers that could be used to drive a transition that supports energy justice. Citizens and elected officials also have too few spaces to exchange and debate. This article presents results form a participatory action research project which aimed at fostering social learning towards energy justice. We deal more specifically with the issues of local political engagement and with social learning approaches that could support territorial transition projects rooted in a vision that is both dialogical and pragmatic.